2020
DOI: 10.1177/1535370220972686
|View full text |Cite
|
Sign up to set email alerts
|

Increased alpha and beta cell mass during mouse pregnancy is not dependent on transdifferentiation

Abstract: Maternal pancreatic beta-cell mass (BCM) increases during pregnancy to compensate for relative insulin resistance. If BCM expansion is suboptimal, gestational diabetes mellitus can develop. Alpha-cell mass (ACM) also changes during pregnancy, but there is a lack of information about α-cell plasticity in pregnancy and whether α- to β-cell transdifferentiation can occur. To investigate this, we used a mouse model of gestational glucose intolerance induced by feeding low-protein (LP) diet from conception until we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Szlapinski et al. showed a significantly increased alpha-cell proliferation at GD 9.5 in mouse pregnancies, resulting in an increased alpha-cell mass at GD 18.5 ( 41 ). Beta-cell proliferation and beta-cell mass were also observed to increase dramatically during the pregnancy ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Szlapinski et al. showed a significantly increased alpha-cell proliferation at GD 9.5 in mouse pregnancies, resulting in an increased alpha-cell mass at GD 18.5 ( 41 ). Beta-cell proliferation and beta-cell mass were also observed to increase dramatically during the pregnancy ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with those observed following transient fasting of non-pregnant mice, where a greater number of transitional α- to β-cells were observed upon re-feeding [ 31 ], resulting in β-cell regeneration and a rescue from diabetes. However, we previously found that α- to β-cell trans-differentiation did not contribute to the increased BCM that normally occurs during mouse pregnancy [ 32 ]. It is possible that the bihormonal cells represent an intermediate stage in the functional maturation of resident β-cell progenitors, which we previously showed to contribute to the increased BCM of pregnancy in mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that pregnancy is accompanied by α-cell mass expansion ( 98 , 99 , 100 ). This effect results from increased α-cell replication but not from transdifferentiation of exocrine cell types ( 100 ).…”
Section: α-Cell Adaptation To Pregnancymentioning
confidence: 99%
“…There is emerging evidence that pregnancy is accompanied by α-cell mass expansion ( 98 , 99 , 100 ). This effect results from increased α-cell replication but not from transdifferentiation of exocrine cell types ( 100 ). However, despite a 2-fold increment of α-cell mass at gestational day 18.5, plasma glucagon levels remain unchanged in pregnant mice ( 98 , 99 , 100 ).…”
Section: α-Cell Adaptation To Pregnancymentioning
confidence: 99%
See 1 more Smart Citation